1998
DOI: 10.1523/jneurosci.18-01-00147.1998
|View full text |Cite
|
Sign up to set email alerts
|

Response of Postmitotic Neurons to X-Irradiation: Implications for the Role of DNA Damage in Neuronal Apoptosis

Abstract: The molecular changes responsible for inducing neuronal apoptosis are unknown. Rat cortical neurons were treated with x-irradiation 7 d after isolation to test for the role of DNA damage in neuronal death. The response of neurons to x-irradiation was compared with that of astrocytes that had been isolated 3 weeks earlier from newborn rats. At the time of irradiation, the neurons appeared well differentiated morphologically and were predominantly (90-95%) noncycling, based on flow cytometric analysis. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
1
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 55 publications
(51 reference statements)
6
92
1
5
Order By: Relevance
“…While control experiments suggested that irradiation did not disrupt hippocampal function beyond limiting proliferation, the possibility remains that unknown molecular factors important to antidepressant efficacy and/or hippocampal function were affected by the procedure. X-ray irradiation of the hippocampus has been shown to cause cognitive deficits in mice (Rola et al, 2004), and may increase apoptosis, produce changes in genes associated with DNA damage and stress response, alter the morphology or functionality of mature neurons, and alter blood flow to irradiated regions (Gobbel et al, 1998;Shirai et al, 2006). Therefore, there remains a need for less invasive methods to test the link between neurogenesis and antidepressant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…While control experiments suggested that irradiation did not disrupt hippocampal function beyond limiting proliferation, the possibility remains that unknown molecular factors important to antidepressant efficacy and/or hippocampal function were affected by the procedure. X-ray irradiation of the hippocampus has been shown to cause cognitive deficits in mice (Rola et al, 2004), and may increase apoptosis, produce changes in genes associated with DNA damage and stress response, alter the morphology or functionality of mature neurons, and alter blood flow to irradiated regions (Gobbel et al, 1998;Shirai et al, 2006). Therefore, there remains a need for less invasive methods to test the link between neurogenesis and antidepressant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that radiation can induce apoptosis in neurons in vivo in newborn animals (Gobbel et al, 1998). Since no such event was found in the CNS of adult rats a direct contribution to the radiation induced CNS toxicity is unlikely.…”
Section: Neuronal Cellsmentioning
confidence: 99%
“…33 In addition, astrocytes express higher amounts of Ref-1 than neurons in the brain. 24 These data together are consistent with an antiapoptotic role for Ref-1 through its DNA repair activity.…”
Section: Loss Of Ref-1 Immunoreactivity Is Associated With Naturally mentioning
confidence: 99%